Rola interwencjonizmu państwowego w powstaniu welfare state w XX wieku - Janik, Robert (Studia Politicae Universitatis Silesiensis, 2018)
Abstract: The role of government intervention in the creation of the “welfare state” in the twentieth century The article deals with issues connected with the shaping of the “welfare state” on the ground of the interventionism. The work was focused upon the following groups of issues: — a genesis of the increase of the state’s protective role in the social area, — creation of a welfare state, and — material and social interdependencies of the existence of a “welfare state” in Europe. In the presentation of the above thematic blocks, a number of phenomena necessary to understand the discussed issues were illustrated, among which some of the most significant ones were: the search for ways to overcome poverty in the industrialization period, the desire to establish a new social-political order in Western European countries in the 20th century, the New Deal, some terminological issues — among others: mutual interdependencies between the “welfare state” and the interventionism, social care model and the competition between the “welfare state” and different ideological attitudes — chiefly the doctrine of neo-liberalism. Key words: government intervention, “welfare state”, interventionism, economical crisis